Correlates of psychopathy in a Tunisian sample of incarcerated women. (August 2021) - Fekih-Romdhane, Feten; Hsini, Ameni; Aouina, Asma Achouri; Ridha, Rym; Cheour, Majda
Abstract: Background: Considerable effort has been devoted to elucidating correlates of psychopathy in males, but only few researchers have turned their attention to this field in female counterparts, with most of the research in this field having been driven from western countries. We aimed to explore psychopathic traits, impulsiveness and psychiatric symptoms that characterize a Tunisian female prison population. Method: Data were collected in a cross-sectional design during September 2017. The sample was comprised of 100 adult females who were incarcerated at the "Manouba Women's Prison" at the time of the survey. The Levenson Self-Report Psychopathy Scale, the Barratt Impulsiveness Scale, and The Brief Symptom Inventory were used. Results: In the univariate analysis, socioeconomic level (p = .001), tobacco use (p = .001), poly drug use (p = .014) and physically aggressive behaviors in the 6 months before incarceration (p = .043) were significantly associated with psychopathy total scores. After multivariable adjustment, motor impulsiveness (β = 0.426, p < .01) and phobic anxiety (β = 0.284, p < .05) contributed significantly to the variance of psychopathy total scores. Conclusion: The current findings not only add to the growing body of literature on female psychopathy, but also help inform decision making about mental health-related programs and policies in female prison settings in underdeveloped and underrepresented countries similar to our sociocultural context. Highlights: Few studies, mostly from western countries, have turned their attention to elucidating emotional, cognitive, and behavioral correlates of psychopathy in females. Studies from under-represented regions may increase our understanding of sociocultural factors that can influence the presentation of psychopathy. We have examined psychopathy among females and in prison setting in a North African country (Tunisia), which represents a double challenge in our cultural context. Socioeconomic status seems to affect the link between substance use and psychopathy in female inmates. Motor impulsivity contributed significantly to both primary and secondary psychopathy. Thus, impulsivity-focused treatment may be beneficial in this specific population Phobic anxiety contributed significantly to psychopathy. Interventions for psychological distress should be specifically designed for women with high psychopathy when aiming to decrease violence.